PENENTUAN KOMPOSISI MEDIA TANAM TERBAIK UNTUK BUDIDAYA SELADA MERAH MENGGUNKANA SISTEM AUTPOT MODIFIKASI - Sophia Dwiratna (Talenta Publisher, 2017)
Autopot an irrigation device which is operated automatically and is capable of providing nutrition in plants without the need for electrical energy. The system is operated via a smart valve that is used to open and close automatically irrigation water by the water conditions in the network system, especially the water level in the network. Basic water level is used as a mechanical sensor for opening and closing the valve automatically without the aid of another power. With these advantages, autopot able to provide water and energy efficiency is very high on a commercial scale hydroponic cultivation. It's just that the system requires very high investment and must be imported. Therefore, this study was conducted to modify the Autopot use of materials and simple equipment and test its performance on the cultivation of red lettuce. Autopot modifications performed on tools, growing media and fertigation systems are smart valve replacement valves using a hole in the bottle that works with pressure and gravity. This study aims to determine the performance test auto pot modification results in the cultivation of red lettuce as well as to determine the ratio of planting media best on auto pot system modifications. Research carried out for 90 days in a greenhouse using descriptive methods. The results showed Autopot Modifications have an average efficiency of the provision of water by 75.86% - 88.05% and an average efficiency of water use by 51.43 kg / m3-88.72 kg / m3, this efficiency is high because of high dihasikan crop production with the use of water low. Planting media between rice husk and humus in the ratio of 50:50 compositions show results better plant growth compared with other growing media composition. plants with irrigation efficiency levels are very high as well minus the electric energy consumption.